Water-based adhesive, aluminum-plastic film and preparation method of aluminum-plastic film

By developing a water-based adhesive and corresponding aluminum-plastic film preparation method, the problem of using organic solvents in the inner layer adhesive in existing lithium battery packaging is solved, and an environmentally friendly and efficient production process and performance is achieved.

CN119799207APending Publication Date: 2025-04-11XINLUN ELECTRONIC MATERIALS CHANGZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411929655.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The inner adhesive used in existing lithium battery packaging mainly relies on organic solvents, which have problems of flammability, explosiveness and environmental pollution, making it difficult to meet the development needs of green and environmental protection.

Method used

Develop an aqueous adhesive to improve the performance and environmental protection of the adhesive by blending the main resin emulsion particles, curing agents and accelerators, combined with a specific process flow.

Benefits of technology

The production of aluminum-plastic film without maturation is achieved, which shortens the production cycle, reduces the use of organic solvents, reduces energy consumption and environmental pollution, and improves the corrosion resistance of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209964250000081
    Figure BDA0005209964250000081
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery packaging, and particularly relates to a water-based adhesive, an aluminum-plastic film and a preparation method of the aluminum-plastic film. The water-based adhesive comprises the following components in percentage by weight: 10-40% of main body blended resin emulsion particles, 1-20% of a curing agent, 0.1-10% of an accelerant, 40-70% of a water solvent and 5-10% of an organic solvent, the main body blended resin emulsion particles comprise one or more of maleic anhydride modified polypropylene butylene, maleic anhydride grafted modified chlorinated polypropylene, maleic anhydride grafted modified POE (Polyolefin Elastomer), maleic anhydride grafted modified SBS (Styrene Butadiene Styrene), chlorinated polypropylene, chlorinated polyethylene, chlorinated polypropylene ethylene and chlorinated polypropylene butylene. According to the water-based adhesive disclosed by the invention, by adjusting the main body blending resin, the curing agent and the accelerant, the defect that the prepared adhesive is short in storage time is effectively overcome. And meanwhile, the accelerant is added, so that the long-term corrosion resistance of the electrolyte under a water-containing condition can be effectively improved. The novel water-based adhesive combination process not only shortens the production cycle, but also can greatly reduce the use of organic solvents, reduces the RTO cost, and reduces the damage to human and environment in the production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery packaging, and specifically relates to a water-based adhesive, an aluminum-plastic film and a preparation method thereof. Background Art

[0002] Lithium battery packaging has become an increasingly widely used packaging form. Its main structure is in the order from inside to outside: inner protective layer, aluminum foil layer and outer protective layer. The inner protective layer usually uses cast polypropylene (CPP). CPP and aluminum foil layer can be compounded together by hot compounding and dry compounding. Hot compounding uses an extruder to co-extrude MPP as an adhesive with CPP on the surface of aluminum foil to obtain bonding strength; dry compounding uses an inner layer adhesive to bond CPP and aluminum foil together.

[0003] Since the main body of the inner layer adhesive is polyolefin, it is not easy to dissolve, so a large amount of flammable, explosive, irritating and other harmful organic mixed solvents must be used to help dissolve it for coating. This method does not conform to the current green and environmental protection development concept. Therefore, it is necessary to develop a more environmentally friendly water-based adhesive for the inner layer bonding of aluminum-plastic film. Summary of the invention

[0004] The purpose of the present invention is to provide a water-based adhesive, an aluminum-plastic film and a preparation method thereof.

[0005] In a first aspect, the present invention provides a water-based adhesive, wherein the components thereof include, by weight percentage:

[0006] The main blend resin latex particles are 10-40%, curing agent is 1-20%, accelerator is 0.1-10%, water solvent is 40-70%, and organic solvent is 5-10%;

[0007] The main blended resin emulsion particles include one or more of maleic anhydride modified polypropylene butene, maleic anhydride grafted modified chlorinated polypropylene, maleic anhydride grafted modified POE, maleic anhydride grafted modified SBS, chlorinated polypropylene, chlorinated polyethylene, chlorinated polypropylene ethylene, and chlorinated polypropylene butene.

[0008] In one embodiment of the present application, the main blended resin emulsion particles include chlorinated polypropylene butene and maleic anhydride modified polypropylene butene.

[0009] Considering that there may be local defects in the surface treatment of aluminum foil, resulting in low bonding strength at this part, chlorinated modified polyolefins with strong bonding strength to aluminum foil are preferred. Considering that the electrolyte swells some polyolefins, resulting in a decrease in cohesive force and failure of bonding strength, and polyolefins with lower melting points are required to achieve easy heating and softening after coating, chlorinated polypropylene butene is preferred.

[0010] Polypropylene butene is used for maleic anhydride modification to give the system a higher polarity. The grafted maleic anhydride can react with the polar molecules on the surface of the passivated aluminum foil to form covalent bonds to enhance adhesion. The maleic anhydride and the curing agent in the system cross-link to enhance cohesion. At the same time, the carbonyl group will also form van der Waals force with the polar groups on the surface of the passivated aluminum foil to improve adhesion.

[0011] In one embodiment of the present application, the mass ratio of the chlorinated polypropylene butene to the maleic anhydride modified polypropylene butene is 3:7 to 6:4.

[0012] In one embodiment of the present application, in order to ensure applicability, the particle size of the main blended resin emulsion particles is 500-1500nm. Too small a particle size leads to high viscosity, which is not conducive to coating. Too large a particle size leads to high viscosity of the emulsion, poor storage stability, low coating density, and poor bonding strength. Further preferably, the particle size of the main blended resin emulsion particles is 600-1100nm.

[0013] In one embodiment of the present application, the melting point of the chlorinated polypropylene butene is 30°C-100°C; more preferably 50°C-70°C.

[0014] In one embodiment of the present application, the chlorinated polypropylene butene chloride content is 0.1%-10.0%. Considering that too low chlorine content leads to low polarity and insufficient bonding strength of aluminum foil, too high chlorine content leads to strong polarity and easy swelling by electrolyte. Further preferably, the chlorinated polypropylene butene chloride content is 0.5%-5.0%.

[0015] In one embodiment of the present application, the melting point of the maleic anhydride grafted polypropylene butene is 30°C-100°C; more preferably 50°C-90°C.

[0016] In one embodiment of the present application, the maleic anhydride grafting rate of the maleic anhydride grafted polypropylene butene is 0.1-5%. Considering that the blend already contains polarity, a too high grafting rate leads to easy swelling by the electrolyte, resulting in a decrease in bonding strength, and a too low grafting rate leads to insufficient subsequent cross-linking reaction with the curing agent, resulting in a decrease in cohesive force and low bonding strength. Further preferably, the maleic anhydride grafting rate of the maleic anhydride grafted polypropylene butene is 0.5-1.5%.

[0017] In one embodiment of the present application, the curing agent is a water-based blocked isocyanate. Water-based blocked isocyanate must be unblocked at a certain temperature to undergo a chemical reaction, thereby avoiding the reaction of the water solvent to the isocyanate group in the mixed adhesive system. After coating, the water is dried and then heated at a high temperature, the active group is released and a cross-linking reaction begins, thereby increasing the curing reaction speed of the system and enhancing the overall bonding strength.

[0018] In one embodiment of the present application, the deblocking temperature of the water-based blocked isocyanate is 50-200°C. Considering that if the deblocking temperature is too low, the resin may be deblocked prematurely during the drying process, while if the deblocking temperature is too high, the main resin may be degraded. Further preferably, the deblocking temperature of the water-based blocked isocyanate is 130-170°C.

[0019] In one embodiment of the present application, the water-based blocked isocyanate has an isocyanate functionality of 1-3 to ensure that the adhesive has a certain stiffness after curing. Considering that too low functionality cannot form effective crosslinking, too high functionality leads to too high three-dimensional network crosslinking, resulting in increased hardness and easy cracking during deep drawing. Further preferably, the isocyanate functionality of the water-based blocked isocyanate is 1.5-2.

[0020] In one embodiment of the present application, the accelerator includes: one or more of zinc octoate, organic tin, organic bismuth catalysts, triethylenediamine, and polymethylaminomethylphenol. The accelerator can catalyze the deblocked isocyanate to undergo dimerization and trimerization, thereby increasing the cohesion and crosslinking density of the cured adhesive, and improving the peel strength and liquid resistance.

[0021] The aqueous solvent is distilled water;

[0022] The organic solvent includes one or more of toluene, acetone, butanone and methylcyclohexane.

[0023] In a second aspect, the present invention provides a method for preparing an aluminum-plastic film, comprising:

[0024] The components of the aqueous adhesive as described above are placed in a solvent and mixed until completely dissolved, the residue is filtered out, and the mixture is applied to the surface of the aluminum foil;

[0025] The solvent is evaporated in an oven, and the film is laminated with the CPP film through a hot pressing roller;

[0026] The composite film is treated with high temperature by a heating roller, and is rapidly cooled by a cold roller at the exit, and then rolled up to room temperature.

[0027] No need for aging, just cut to the required size and it can be shipped directly.

[0028] In one embodiment of the present application, after corona treatment, the dyne value of the CPP film is 30-50, preferably 38-48. More preferably, it is 40-46. If the dyne value is too low, the CPP surface active groups are too few, the crosslinking degree with isocyanate is too low, and the surface roughness is insufficient, and the blended modified polyolefin cannot form sufficient anchoring with it, resulting in low peel strength; if the dyne value is too high, the CPP surface will be too rough and affect the appearance.

[0029] In one embodiment of the present application, the actual coating amount of the inner layer of adhesive after drying is 1.0 g / ㎡-4.0 g / ㎡, preferably 2.5 g / ㎡-3.5 g / ㎡, and more preferably 2.7 g / ㎡-3.3 g / ㎡.

[0030] In one embodiment of the present application, the temperature of the hot pressing roller when the CPP film is compounded with the aluminum foil is controlled at 50-150°C, preferably 80-130°C, and more preferably 100-120°C. At the same time, the pressure is 0.1Mpa-1.5Mpa, preferably 0.5Mpa-1.3Mpa, and more preferably 0.6Mpa-1.0Mpa. If the temperature is too low, the adhesive cannot melt and fuse with the CPP, and if the temperature is too high, the blocked isocyanate will unblock and react prematurely. If the pressure is too low, the adhesive layer cannot be compacted on the aluminum foil; if the pressure is too high, wrinkles may easily appear.

[0031] In one embodiment of the present application, the high temperature heat treatment temperature of the composite film is controlled at 100°C-200°C, preferably 130-180°C, and more preferably 150-170°C. If the temperature is too low, the blocked isocyanate cannot be unblocked, and the accelerator cannot catalyze the formation of dimers and trimers; if the temperature is too high, the adhesive itself will be degraded, the cohesive force will decrease, and the later electrolyte peeling strength will be affected. At the same time, excessive melting will cause bubbles to form on the CPP surface.

[0032] In a third aspect, the present invention further provides an aluminum-plastic film, which is prepared by the aluminum-plastic film preparation method as described above.

[0033] The beneficial effect of the present invention is that the water-based adhesive of the present invention effectively solves the defect of short storage time of the prepared adhesive by adjusting the main blended resin, curing agent and accelerator. At the same time, by adding the accelerator, the long-term corrosion resistance of the electrolyte under water conditions can be effectively improved. By adjusting the production line process, not only can the 4d aging time be shortened and a large amount of energy consumption can be saved, but the performance can also fully reach the level of normal products. The new water-based adhesive combined process not only shortens the production cycle, but also can greatly reduce the use of organic solvents, reduce RTO costs, and reduce damage to people and the environment during the production process.

[0034] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description.

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] The raw materials of the water-based adhesive include: 25% of main blended resin latex particles, 1.7% of curing agent, 0.8% of accelerator, 62.5% of water solvent and 10% of organic solvent.

[0039] The main blended resin emulsion particles include: chlorinated polypropylene butene (A), with a chlorine content of 10% and a melting point of 60°C; maleic anhydride modified polypropylene butene (B), with a grafting rate of 1% and a melting point of 70°C; the mass ratio of A to B is 5:5. The emulsion particle size is controlled at 900-1100nm.

[0040] Among them, the curing agent is a blocked isocyanate with a deblocking temperature of 130°C and a functionality of 1.8;

[0041] Among them, the accelerator is polymethylaminomethylphenol;

[0042] Among them, the aqueous solvent is distilled water, and the organic solvent is toluene.

[0043] Place all components in a solvent and mix until completely dissolved, filter out the residue, apply it on the surface of aluminum foil, pass through an oven to evaporate the solvent, and composite it with a CPP film with a dyne value of 38 through a hot pressing roller. The composite film is subjected to high-temperature treatment by a heating roller, and is quenched at the exit by a cold roller, and is rolled up at room temperature. It does not need to be aged and can be directly shipped after being cut to the required size.

[0044] Among them, the actual coating amount of the inner layer glue after drying is 2.9g / ㎡;

[0045] Among them, the oven temperature is 100°C;

[0046] Among them, the thermal lamination temperature of cast polypropylene film and aluminum foil is 100°C, and the thermal lamination pressure is 0.9Mpa;

[0047] The heat treatment temperature of the heating roller is 160°C.

[0048] Embodiment 2

[0049] The raw materials of the water-based adhesive include: 20% of main blended resin latex particles, 1.5% of curing agent, 0.5% of accelerator, 70% of water solvent and 8% of organic solvent.

[0050] The main blended resin emulsion particles include: chlorinated polypropylene butene (A), with a chlorine content of 5% and a melting point of 55°C; maleic anhydride modified polypropylene butene (B), with a grafting rate of 0.8% and a melting point of 75°C; the mass ratio of A to B is 4:6. The emulsion particle size is controlled at 900-1100nm.

[0051] Among them, the curing agent is a blocked isocyanate with a deblocking temperature of 150°C and a functionality of 2;

[0052] Among them, the accelerator is polymethylaminomethylphenol;

[0053] Among them, the aqueous solvent is distilled water, and the organic solvent is toluene.

[0054] Place all components in a solvent and mix until completely dissolved, filter out the residue, apply it on the surface of aluminum foil, pass through an oven to evaporate the solvent, and composite it with a CPP film with a dyne value of 38 through a hot pressing roller. The composite film is subjected to high-temperature treatment by a heating roller, and is quenched at the exit by a cold roller, and is rolled up at room temperature. It does not need to be aged and can be directly shipped after being cut to the required size.

[0055] Among them, the actual coating amount of the inner layer glue after drying is 2.9g / ㎡;

[0056] Among them, the oven temperature is 100°C;

[0057] Among them, the thermal lamination temperature of cast polypropylene film and aluminum foil is 100°C, and the thermal lamination pressure is 0.9Mpa;

[0058] The heat treatment temperature of the heating roller is 170°C.

[0059] Comparative Example 1

[0060] The applicant currently has a comparative test of dry composite process technology products using solvent-based inner layer adhesives.

[0061] The solvent-based inner layer adhesive is coated on the surface of the aluminum foil and dried in an oven. The CPP film is attached to the aluminum surface for hot pressing and aging. After aging, the performance test is performed.

[0062] Among them, the actual coating amount of the inner layer glue after drying is 3.2g / ㎡;

[0063] Among them, the oven temperature is 90°C;

[0064] Among them, the thermal lamination temperature of cast polypropylene film and aluminum foil is 110°C, and the thermal lamination pressure is 0.7Mpa;

[0065] Among them, the aging temperature is 40°C and the aging time is 4 days.

[0066] Comparative Example 2

[0067] The applicant conducted a comparative test on the existing thermal composite technology products, in which maleic anhydride grafted modified polypropylene was co-extruded with polypropylene, and the maleic anhydride grafted modified polypropylene was directly cast on the surface of aluminum foil, cooled to room temperature by a cold roller to allow it to crystallize, and then heated at high temperature to activate the maleic anhydride therein to cause it to react with the active functional groups on the surface of the aluminum foil, and then cooled to room temperature for performance testing.

[0068] Wherein, the heating temperature is 190°C;

[0069] The aluminum-plastic films obtained in the above Examples 1-2 and Comparative Examples 1-2 were used to perform an initial peel test of AL / PP and a long-term corrosion peel test of AL / PP under aqueous electrolyte conditions, wherein the CPP film layer was 40 μm thick.

[0070] The test sample was cut into a size of 15 mm in width and 100 mm in length. The test environment of the electrolyte was a high temperature of 85°C.

[0071] The test data is as follows:

[0072]

[0073] The evaluation results show that the present invention improves the formula of water-based adhesives and adjusts the production line process, which can not only shorten the 4-day aging time and save a lot of energy consumption, but also fully reach the performance level of normal products. The new water-based adhesive combined process not only shortens the production cycle, but also greatly reduces the use of organic solvents, reduces RTO costs, and reduces damage to people and the environment during the production process.

[0074] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A water-based adhesive, characterized in that: Its components include by weight percentage: The main blend resin latex particles are 10-40%, curing agent is 1-20%, accelerator is 0.1-10%, water solvent is 40-70%, and organic solvent is 5-10%; The main blended resin emulsion particles include one or more of maleic anhydride modified polypropylene butene, maleic anhydride grafted modified chlorinated polypropylene, maleic anhydride grafted modified POE, maleic anhydride grafted modified SBS, chlorinated polypropylene, chlorinated polyethylene, chlorinated polypropylene ethylene, and chlorinated polypropylene butene.

2. The water-based adhesive according to claim 1, characterized in that: The main blended resin emulsion particles include chlorinated polypropylene butene and maleic anhydride modified polypropylene butene; The mass ratio of the chlorinated polypropylene butene to the maleic anhydride modified polypropylene butene is 3:7 to 6:

4.

3. The water-based adhesive according to claim 1, characterized in that: The particle size of the main blended resin emulsion particles is 500-1500nm.

4. The water-based adhesive according to claim 1, characterized in that: The melting point of the chlorinated polypropylene butene is 30°C-100°C; The chlorinated polypropylene has a butylene chloride content of 0.1%-10.0%.

5. The water-based adhesive according to claim 1, characterized in that: The melting point of the maleic anhydride grafted polypropylene butene is 30°C-100°C; The maleic anhydride grafting rate of the maleic anhydride grafted polypropylene butene is 0.1-5%.

6. The water-based adhesive according to claim 1, characterized in that: The curing agent is a water-based blocked isocyanate; The deblocking temperature of the water-based blocked isocyanate is 50-200°C.

7. The water-based adhesive according to claim 6, characterized in that: The isocyanate functionality of the water-based blocked isocyanate is 1-3.

8. The water-based adhesive according to claim 1, characterized in that: The accelerator includes: one or more of zinc octoate, organic tin, organic bismuth, triethylenediamine, and polymethylaminomethylphenol; The aqueous solvent is distilled water; The organic solvent includes one or more of toluene, acetone, butanone and methylcyclohexane.

9. A method for preparing an aluminum-plastic film, characterized in that: include: The components of the water-based adhesive according to any one of claims 1 to 8 are placed in a solvent and mixed until completely dissolved, the residue is filtered out, and the mixture is applied to the surface of the aluminum foil; The solvent is evaporated in an oven, and the film is laminated with the CPP film through a hot pressing roller; The composite film is treated with high temperature by a heating roller, and is rapidly cooled by a cold roller at the exit, and then rolled up to room temperature.

10. An aluminum-plastic film, characterized in that: The aluminum-plastic film is prepared by the method for preparing the aluminum-plastic film as claimed in claim 9.